Description of a new species of the genus Lutzomyia França, 1924 (Diptera: Phlebotominae) and of the male of Lutzomyia fonsecai (Costa Lima, 1932) - Júnior, Salvador P. Chaves; Lima, Guilherme C.; Mendonça, Rafael P.; Andrade, Andrey J. (Zootaxa, 2023)
Lutzomyia itambe sp. n. is described as a new species of neotropical cavernicolous phlebotomine sand fly based on specimens of males and females collected in the Gruta do Itambé, Altinópolis municipality, São Paulo State. In addition to this, we describe the male of Lutzomyia fonsecai (Costa Lima, 1932) collected near their type-locality in Bolivia. These descriptions are supported by illustrations that detail the morphological and morphometrical characteristics of the specimens. Lutzomyia itambe sp. n., L. fonsecai, along with L. dispar Martins & Silva, 1963, comprise the already named “Fonsecai complex”. Both sex present parallel labial sutures, not forked, and males can be differentiated by parameral characters, while in females the distinction is made by characters of the palpi and spermathecae.